Self-Assembly of an Organized Cementum-Periodontal Ligament-Like Complex Using Scaffold-Free Tissue Engineering - Basu, Avik; Rothermund, Kristi; Ahmed, Meer N.; Syed-Picard, Fatima N. (Frontiers in Physiology, 2019)
A major challenge in regenerating periodontal tissues is emulating its complex structure containing both mineralized and soft tissues. In this study, scaffold-free tissue constructs engineered using periodontal ligament cells (PDLCs), which contain a population of adult stem/progenitor cells, self-assembled into an organized multi-tissue structure comprising a mineralized cementum-like core enclosed within a periodontal ligament (PDL)-like tissue. Scaffold-free engineered constructs were formed by culturing human PDLCs to form a cell sheet on 6-well dishes containing two minutien pins placed 7 mm apart. The cell sheet was contracted by the cells to roll into the pins forming a cylindrical construct anchored on either end by the pins. These tissues were approximately 1 mm in diameter and 7 mm long and contained only the cells and their endogenous matrix. These scaffold-free engineered constructs exhibited two structurally distinct tissues, one in the center of the construct and another on the periphery. The center tissue was mineralized and expressed alkaline phosphatase and bone sialoprotein, similar to cementum. The peripheral tissue was not calcified and expressed periodontal ligament associated protein-1 and periostin, which is characteristic of the periodontal ligament. This tissue organization was seen after in vitro culture and maintained in vivo following subcutaneous implantation in immunocompromised mice. These data demonstrate that scaffold-free tissue engineering facilitates PDLCs to self-assemble into an organized cementum-PDL-like complex. These engineered tissues could be used as implantable grafts to regenerate damaged periodontal tissues or as model systems to study PDLC biology and mechanisms driving organized tissue assembly within the periodontium.